actually....u cannot solve an expression...u can solve only an equation and i think in ur case , the q should be if a + b + c = 0 ...so raju,,,has done all the hard work for you.....its 100% correct... and make sure u thank him by voting as the best answer
2006-12-08 16:28:23
·
answer #1
·
answered by mr_BIG 3
·
0⤊
0⤋
You have not specified the variable you are trying to solve for; in fact, 3abc-a^3+b^3+c^3 is only an expression, not an equation.
2006-12-08 05:11:20
·
answer #2
·
answered by Bugmän 4
·
0⤊
0⤋
I guess what he asking. if a+b+c = 0 Then 3abc-a^3+b^3+c^3 =0
a+b+c = 0
(a+b) =- c
(a+b)^3 = -c^3
a^3+b^3+3ab(a+b) = -c^3
since a+b = -c
a^3+b^3+3ab(-c) = -c^3
a^3+b^3+c^3 - 3abc =0
or a^3+b^3+c^3 = 3abc
2006-12-08 12:35:23
·
answer #3
·
answered by raju 5
·
1⤊
0⤋
a^3+b^3+3ab(a+b) = -c^3
since a+b = -c
a^3+b^3+3ab(-c) = -c^3
a^3+b^3+c^3 - 3abc =0
or a^3+b^3+c^3 = 3abc
got ti......
2006-12-09 06:51:25
·
answer #4
·
answered by Hemali 2
·
0⤊
0⤋
This is not a equation.
2006-12-08 06:21:59
·
answer #5
·
answered by freemind 2
·
0⤊
0⤋
post the full question.............
2006-12-08 05:14:13
·
answer #6
·
answered by nothingspecial 1
·
0⤊
0⤋
post the full question.............
2006-12-08 05:11:43
·
answer #7
·
answered by mohit 2
·
0⤊
0⤋